STRATEGI PENINGKATAN KINERJA KEPOLISIAN DALAM MEMBENTUK BUDAYA ORGANISASI - Tugimin Supriyadi; Onik Wahyu Utami, Lani Pranesti, Hening Tyas Arridho, Alfalah Putri Nura’rafah (ADMIN: Jurnal Administrasi Negara, 2025)
This research investigates ways to improve police performance by creating a strong organizational culture. When it comes to policing, a strong culture is essential for optimal performance. Leaders are also very important in providing good examples and establishing vision and mission. This research shows how important it is for all workers to commit to building a culture that supports high performance. As a result, it is hoped that the police can act more responsive, fair and professional.